Assessment of the relationship between living alone and suicidal behaviors based on prospective studies: a systematic review and meta-analysis - Luo, Zhipeng; Wang, Jinfeng; Chen, Xu; Cheng, Dejin; Zhou, Yuanyuan (Frontiers in Public Health, 2024)
Suicide, a global health concern, can be influenced by living arrangements. Hence, the objective of this systematic review was to assess the extent of the association between living alone and suicidal behaviors. We conducted a comprehensive search across eight databases for prospective studies. Hazard ratios (HR) and 95% confidence intervals were pooled using Stata software. Nine large-scale prospective studies with 3,663,205 participants proved eligible. The results of the meta-analysis showed that the pooled prevalence of living alone was 32%. Living alone was associated with suicide attempts and suicide death even after adjusting for all potential confounding factors (AHR = 1.45, 95% CI: 1.13–1.77; AHR = 1.27, 95% CI: 1.06–1.48). Compared to people who live with others, living alone increases the risk of suicide behaviors. Given the anticipated global rise in suicide rates and the growing prevalence of living alone, it is recommended to explore this issue on a broader scale. Systematic review registration: PROSPERO, identifier: CRD42023464684, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023464684.